Sistem Informasi Penjualan dan Stock Bahan Baku Berbasis Web (Studi Kasus Pabrik Krupuk Berkah Jaya) - Alfan Rosid, Mochamad; Ardiansyah, Alfinas (Indonesian Journal Publisher, 2024)
This research departs from the researcher's interest in the function of websites in the sales process and stock of raw materials at a cracker factory. This research aims to develop an information system that can improve structured data management in business processes, especially in matters regarding sales and stock of raw materials. This research uses the Waterfall method as a development method. The data collection method in this research was carried out using observation, interviews and documentation techniques. The results of this research show that the existence of a website-based information system or sales and raw material recording system facilitates various transaction processes at this cracker factory. Having a database system compiled on a website will make it easier for an owner or business actor to store information on buying and selling transactions, record raw materials, and will make it easier to make reports..